Sustainable Urban Transport for Kyiv : Towards a Sustainable and Competitive City Built Upon the Legacy System and Innovations - World Bank Group (World Bank, Washington, DC, 2016)
This report presents the scope and findings of the Economic Sector Work on Sustainable Urban Transport for the City of Kyiv, financed jointly by the Energy Sector Management Assistance Program (ESMAP) and the Korea Green Growth Trust Fund (KGGTF). The analysis consists of a rigorous evidence-based review of the strengths and weaknesses of Kyiv’s public transport system and a proposed plan improve its network and operational efficiency. It directly addresses the City Administration’s aim to develop practically-focused proposals for optimizing Kyiv’s public transport networks so as to improve their operational and environmental efficiency, minimize costs for operators, and maximize connectivity. These proposals also take into account the future land use plan for the city. The analytical work, requested by KSCA, aimed to support Kyiv City Administration (KCA) in improving the mobility conditions in Kyiv though practically-focused recommendations on public transport service optimization and reorganization. The proposed optimization plans and reforms aim to tackling the operational and capacity deficiencies that are routinely experienced on the local public transport networks during peak hours. The analytical work benefited from a solid partnership with KCA and other stakeholders and aim to reflect a common view on the proposed measures and their implementation. This report summarizes the analyses, findings and recommendations that emerged from the assessment and optimization plans. The remaining of this report is organized as follows: Chapter 2 presents the assessment of the current mobility conditions in Kyiv. It presents the results of an evidence based and data driven assessment of the demand and supply for public transport and the results of a benchmarking analysis comparing key variables among cities with comparable characteristics. Chapter 3 presents the optimization plans. It includes the principles applied during the optimization process and the resulting scenarios as well as their estimated impacts on users’ mobility, suppliers’ operations and the environment.Chapter 4 discusses key aspects of a sustainable transport roadmap. The chapter discusses issues related to the implementation of the optimization plans as well as broader aspects related to the overall improvement of the mobility conditions such as priority investments, traffic management and control, parking and integrated planning.